2015
DOI: 10.1186/s40659-015-0057-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of MCP-1-CCR2 ligand-receptor axis in chondrocyte degradation and disease progress in knee osteoarthritis

Abstract: Background Osteoarthritis (OA) is a common arthritic disease and multifactorial whole-joint disease. Interactions of chemokines and OA is inadequately documented.Results In vivo and in vitro studies were conducted to investigate monocyte chemoattractant protein 1 (MCP-1) and receptor chemokine (C–C motif) receptor 2 (CCR2) in chondrocyte degradation and cartilage degeneration. Chondrocytes from 16 OA patients and 6 normal controls were involved in this study. After stimulation of MCP-1, the expression of MCP-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 27 publications
2
59
0
1
Order By: Relevance
“…In the context of OA, previous studies demonstrated that chondrocytes upregulate CCL2 expression following inflammatory stimuli 17 27 28. Consistent with this, we found that chondrocytes within OA cartilage tissues abundantly express CCL2 (see online supplementary figure S4E).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In the context of OA, previous studies demonstrated that chondrocytes upregulate CCL2 expression following inflammatory stimuli 17 27 28. Consistent with this, we found that chondrocytes within OA cartilage tissues abundantly express CCL2 (see online supplementary figure S4E).…”
Section: Resultssupporting
confidence: 89%
“…While it is known that CCL2 is predominantly made by immune cells in humans and mice, other non-immune cell types have also been shown to express CCL2. For instance, previous studies have demonstrated that cultured murine and human chondrocytes upregulate CCL2 expression following inflammatory stimuli 27 28. Furthermore, it is well known that ageing, a major risk factor for OA development, is associated with systemic low-grade inflammation including elevated local and circulating cytokines 43.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, IL-6 is described to be able to increase MMP expression alone or in synergy with IL-1β and oncostatin M [83][84][85]. In addition, MCP-1 increased MMP-13 expression in chondrocytes [86]. Furthermore, several other proteins that are abundantly present in L-PRF CM, such as RANTES, growth regulated oncogene (GRO) and IL-8 might be responsible for the observed effects in our study [31].…”
Section: Discussionsupporting
confidence: 48%
“…In subjects suffering from OA there is a reduction in antioxidants [47]. Proinflammatory cytokines (IL-1β, IL-6, and TNF-α), chemokines (MIP-Iα and MIP-2), and NO also play an important function in the pathogenesis of joint damage [48][49][50]. In this regard, in this study, it was found that in rats with OA, treated with carnosine or HA or carnosine+HA, the levels of pro-inflammatory cytokines and chemokines were not significantly reduced.…”
Section: Discussionmentioning
confidence: 99%